Arthroscopic Single‐row versus Double‐row Technique for Repairing Rotator Cuff Tears: a Systematic Review and Meta‐analysis. Issue 4 (November 2014) - Ying, Zhi‐min; Lin, Tiao; Yan, Shi‐gui
<x xml:space="preserve">Abstract</x> Objective The purpose of this study was to systematically review published reports that compare the outcomes of single‐row and double‐row suture anchor fixation in arthroscopic rotator cuff repair. Methods Combined data regarding relevant patient characteristics, rotator cuff pathology, surgical techniques, postoperative rehabilitation regimens, University of California at Los Angeles (UCLA) Scores, Constant scores, American Shoulder and Elbow Society (ASES) scores, tendon healing, incidence of recurrent rotator cuff defects, shoulder muscle strength, range of motion, surgical time and patient satisfaction were assessed. Results Seven eligible randomized controlled studies and four prospective cohort studies were identified. There were no significant differences between the single‐row and double‐row groups in terms of Constant or ASES scores. However, UCLA scores, tendon healing, abduction shoulder strength index (SSI), external rotation SSI and internal rotation SSI were significantly better for double‐row technique than for single‐row technique. A statistically significant advantage for double‐row repair according to UCLA score and external rotation SSI was found in the subgroup with tears greater than 3 cm. Conclusion No definite conclusion could be drawn about differences in overall outcomes of double‐ and single‐row techniques for repairing for small to medium (<3 cm) or large to massive (>3 cm) rotator cuff tears, even though some measures of clinical outcome showed significant differences between these two techniques.